(untitled) (Development Service Industry Management, 2025)
In the modern transformational environment of the Ukrainian healthcare system, there is a growing need to rethink approaches to the management of medical institutions and the effective use of resources in the context of decentralization, financial autonomy and social responsibility. The article provides an in-depth analysis of management patterns in the Ukrainian healthcare system, taking into account the challenges caused by public administration reform, economic decentralization, financial instability and the COVID-19 pandemic. Particular attention is paid to the concept of public-private partnership as a tool for integrating the interests of the state, business and community in the process of managing medical institutions and developing healthcare infrastructure. Based on the analysis of scientific works, statistical data and international experience, key management models have been identified that demonstrate high efficiency in ensuring the accessibility, quality and innovation of medical services. The study covers both centralized and decentralized forms of management, focusing on the combination of administrative and market mechanisms that allow increasing the adaptability of the healthcare system to external changes. The mechanisms for implementing partnership models through foresight approaches, strategic planning, implementation of technological roadmaps, development of social capital and attraction of private investments in the field of medicine are considered. The role of the system of quality control of medical services and methods of assessing the effectiveness of management decisions, which have become especially relevant in the context of the pandemic, are also examined. The advantages of models based on multi-actor interaction and stable institutional mechanisms that can ensure not only short-term improvements, but also long-term stability and sustainability of the industry are summarized. A typology of management patterns is proposed, practical recommendations are formulated for the formation of partnership platforms at the regional level, the development of human resources and the digital transformation of management in the medical sector. The results obtained are of great importance for the further development of strategies for reforming healthcare in Ukraine, ensuring transparency of processes, effective use of resources and strengthening public trust in the system.